Pyramid visualization applied to export performance - Lagunas Puls, Sergio; Oropeza Tagle , Miguel Angel; Soto Pérez, Brenda Lizeth (Latin American Journal of Trade Policy, 2024)
The objective is to visualize the performance of Mexican exports of petroleum oils, for the years from 2002 to 2021. Balassa Index is an indicator that is used to measure export performance for a given product compared against the total of exports from one country to another. A four-sided pyramidal model is used; it is built from the results of the Balassa Index (IB), being the height of the pyramid, the overall performance and the base is the BI for each destination. Data of exports of petroleum oils, heading 27.10 to the United States of America, Brazil, Colombia and Guatemala are used. Finally, a dynamic model is proposed by using regression equation. The results show that pyramids allow to adequately visualize the performance of the analysed exports, in addition, the described methodology allows its application to any tariff code.